DEKONSTRUKSI ANGAN-ANGAN SOSIAL DARI PERSPEKTIF ARKOUN HINGGA AL-JABIRY - Nuruddin, Nuruddin (el-Umdah, 2022)
In deconstructing social imagination, the author uses the perspectives of Muhammed Arkoun to Al-Jabiry as an effort to dismantle the reason which still has a negative role for the people. The social ideas that must be deconstructed are myths, rituals, ideologies, norms, values, beliefs, and orthodox-dogmatic systems of thought. So to answer it all, for Arkoun it must be deconstructed using social sciences reasoning; philosophy, anthropology, sociology, psychology, and language in order to find an epistemological reality that is more modern, inclusive, and not frozen anymore. While deconstruction for al-Jabiry is used objectivity and rationality. Objectives means to make tradition more contextual with itself, from our present condition, which means to free oneself from apriori assumptions about tradition and the desires of the present, by separating the subject of the study and the object being studied. Meanwhile, rationality is to make the tradition more contextual with our present conditions by connecting the object and subject of the study in order to obtain a holistic reading of the tradition.